2006
DOI: 10.1111/j.1464-410x.2006.06509.x
|View full text |Cite
|
Sign up to set email alerts
|

Visually directed high‐intensity focused ultrasound for organ‐confined prostate cancer: a proposed standard for the conduct of therapy

Abstract: None had had previous hormone therapy and all had ≥ 3-month PSA nadirs recorded at the follow-up. Nine men were treated using an algorithm-based protocol (group 1) and 25 using visually directed therapy (group 2). The conduct of visually directed treatment was described and changes seen using B-mode US were categorized using three 'Uchida' grades. RESULTSThe mean PSA nadir achieved in group 2 was 0.15 ng/mL, vs 1.51 ng/mL in group 1 ( P < 0.005). In group 2, 21 of 25 men achieved PSA nadirs of ≤ 0.2 ng/mL 3 mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(41 citation statements)
references
References 25 publications
0
41
0
Order By: Relevance
“…18 For prostate cancer, ultrasound imaging has recently been suggested and used as a noninvasive temperature monitoring system for improving treatment heating patterns with HIFU devices by adjusting the treatment parameters between pulses. 15 Regardless of the method used to monitor and control HIFU prostate thermal therapy, the heating requires significantly long treatment times for prostate cancer ͑169 min average 5 ͒. When monitoring the temperature with MR, the cost and resources involved can become significant with this long treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18 For prostate cancer, ultrasound imaging has recently been suggested and used as a noninvasive temperature monitoring system for improving treatment heating patterns with HIFU devices by adjusting the treatment parameters between pulses. 15 Regardless of the method used to monitor and control HIFU prostate thermal therapy, the heating requires significantly long treatment times for prostate cancer ͑169 min average 5 ͒. When monitoring the temperature with MR, the cost and resources involved can become significant with this long treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Transrectal high-intensity focused ultrasound ͑HIFU͒ devices offer a high degree of control over the creation of a thermal lesion in the prostate, 5,13,14 and recent advancements in ultrasound imaging-based treatment monitoring may further improve treatment results. 15 However, transrectal HIFU devices require significant treatment times to ablate large volumes and face difficulties targeting the anterior portion of the gland. 5 Magnetic resonance ͑MR͒ imaging techniques are being investigated for noninvasive monitoring of thermal therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Although our results suggest that MRI adds little to the use of PSA in the routine monitoring of patients for residual or recurrent disease after HIFU, it has the fundamental advantage that it may be used to localise the tumour. Indeed, Rouvière et al [10] have recently shown that biopsies targeted to areas of suspicion on post-HIFU (Ablatherm device) DCE-MRI were 3.35 times more likely to be positive for tumour than untargeted cores [11].…”
Section: Dce-mri Vs Psa For Detection Of Disease After Hifu Of Prostamentioning
confidence: 99%
“…All included patients underwent treatment using the whole-gland HIFU technique as previously described [11,12].…”
Section: Whole-gland High-intensity Focused Ultrasound Treatmentmentioning
confidence: 99%
“…Five of the first six patients treated were failures, and this was with proctors present. We are part of the European user group and at the quarterly trial meetings, it was agreed that we should move from low power treatments to high power treatments [5], use suprapubic catheters in preference to urethral and amend bowel preparation to help prevent the chance of fistulae. All these changes were made during the trial and thus skewed the data.…”
Section: W R I T E T O T H E E D I T O R B Y S U B M I T T I N G Y O mentioning
confidence: 99%